A P300 Brain-Computer Interface Paradigm Based on Electric and Vibration Simple Command Tactile Stimulation - Chu, Chenxi; Luo, Jingjing; Tian, Xiwei; Han, Xiangke; Guo, Shijie (Frontiers in Human Neuroscience, 2021)
This paper proposes a novel tactile-stimuli based P300 paradigm for Brain-Computer Interface (BCI), with only one target site stimulated in each block. It features a combination of spatial and frequency information, using the spatial information identifying the sites of stimuli and frequency information distinguishing target stimuli and non-target stimuli. A classification algorithm has also been developed by introducing filters with selected frequency bands and conducting optimization with common spatial pattern (CSP) on the tactile evoked EEG signals. We investigated both electrical stimulation and vibration stimulation in twenty healthy subjects. The results demonstrated an average accuracy of 94.88% for electrical stimuli and 95.21% for vibration stimuli, respectively. Together with its simpleness, this paradigm is particularly suitable for the elderly and people with less learning ability and difficulties in long-term concentration, e.g. stroke and dementia patients.